ANALISIS PENGEMBANGAN KAWASAN PARIWISATA PANTAI MOALE - Mulia, Endi Martha; Napitupulu, Binur Pretty; Siahaan, Rikardo H.; Purba, Swingly; Ndruru, Markus (Jurnal Ilmiah Akomodasi Agung, 2022)
In the development of extensive attractions in South Mias, the government has a very important role in organizing, monitoring and formulating and implementing the target and accurate target development policy according to the need to solve problems in the development of tourism. Therefore the development of the tourist object in effective and efficient tourism development, should be implemented well as the purpose of improving and preserving potential of the tourist object. This is aimed at knowing how the implementation of the Moala Beach Tourism Development policy implementation in South Nias Division. The research method used in this study is a qualitative descriptive method to illustrate the actual phenomenon of the incident. The data collection uses the interviews, observation and documents related to research. The theory used is the model of implementation of Richardson and Fluker consisting of 6 variables: Size and purpose of policy, resources, implementation body characteristics, communication between the executive bodies, social environment, economic, and political conditions and implementation (dispositions). The results of the study show that the implementation of the Moala Beach's attractions for the development of the Mole Park has yet to be implemented well because it is difficult to build communication with local communities in terms of cooperation to preserve and support the development process and the implementation of the program program. At the implementation of this policy there are still kebalas on less sufficient human resources and coordination with other unforced detail as due to the local sectoral ego that considers that the development task is the task of the associated duty.